Assessment of molecularly imprinted polymers (MIPs) in the preconcentration of disperse red 73 dye prior to photoelectrocatalytic treatment - Franco, Jefferson Honorio [UNESP]; Aissa, Alejandra Ben; Bessegato, Guilherme Garcia [UNESP]; Fajardo, Laura Martinez; Zanoni, Maria Valnice Boldrin [UNESP]; Pividori, María Isabel; Del Pilar Taboada Sotomayor, Maria [UNESP] (Springer Nature, 2017)
Magnetic molecularly imprinted polymers (MMIPs) have become a research hotspot due to their two important characteristics: target recognition and magnetic separation. This paper presents the preparation, characterization, and optimization of an MMIP for the preconcentration of disperse red 73 dye (DR73) and its subsequent efficient degradation by photoelectrocatalytic treatment. The MMIPs were characterized by scanning electron microscopy (SEM), which revealed homogeneous distribution of the particles. Excellent encapsulation of magnetite was confirmed by transmission electron microscopy (TEM). A study of dye binding showed that the dye was retained more selectively in the MIP, compared to the NIP. The release of DR73 from the imprinted polymers into methanol and acetic acid was analyzed by UV-Vis spectrophotometry. The extracts showed higher absorbance values for MMIP, compared to MNIP, confirming greater adsorption of dye in the MMIP material. The extracts were then subjected to photoelectrocatalytic treatment. LC-MS/MS analysis following this treatment showed that the dye was almost completely degraded. Hence, the combination of MMIP extraction and photoelectrocatalysis offers an alternative way of selectively removing an organic contaminant, prior to proceeding with its complete degradation.
Keywords: Adsorption; Advanced oxidation process; Molecularly imprinted polymers; Photoelectrocatalytic oxidation; Textile dye degradation; Wastewater treatment